Human genetic variation and the genotype-phenotype problem 2 - Lyon, Gholson (Henry Stewart Talks, 2015)
The biology of mental defect, Documentation of Down syndrome, Variable expressivity of disease, Mutations as "difference makers", The "map making" stage, Mutation without disease in “disease genes”, Overly simplistic view of "genes causing autism", Rare variants in rare and common diseases, Mutations modulated by genetic background, Clinical validity through “Networking of science"